Effects of Gestational Inflammation with Postpartum Enriched Environment on Age-Related Changes in Cognition and Hippocampal Synaptic Plasticity-Related Proteins - Shi-Yu Sun; Xue-Yan Li; He-Hua Ge; Yu-Xin Zhang; Zhe-Zhe Zhang; Zhan-Qiang Zhuang; Chong-Yang Ren; Fang Wang; Gui-Hai Chen (Neural Plasticity)
Increasing evidence indicates that exposure to inflammation during pregnancy intensifies the offspring’s cognitive impairment during aging, which might be correlated with changes in some synaptic plasticity-related proteins. In addition, an enriched environment (EE) can significantly exert a beneficial impact on cognition and synaptic plasticity. However, it is unclear whether gestational inflammation combined with postnatal EE affects the changes in cognition and synaptic plasticity-related proteins during aging. In this study, pregnant mice were intraperitoneally injected with lipopolysaccharides (LPS, 50 μg/kg) or normal saline at days 15–17 of pregnancy. At 21 days after delivery, some LPS-treated mice were randomly selected for EE treatment. At the age of 6 and 18 months, Morris water maze (MWM) and western blotting were, respectively, used to evaluate or measure the ability of spatial learning and memory and the levels of postsynaptic plasticity-related proteins in the hippocampus, including postsynaptic density protein 95 (PSD-95), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) GluA1 subunit, and Homer-1b/c. The results showed that 18-month-old control mice had worse spatial learning and memory and lower levels of these synaptic plasticity-related proteins (PSD-95, GluA1, and Homer-1b/c) than the 6-month-old controls. Gestational LPS exposure exacerbated these age-related changes of cognition and synaptic proteins, but EE could alleviate the treatment effect of LPS. In addition, the performance during learning and memory periods in the MWM correlated with the hippocampal levels of PSD-95, GluA1, and Homer-1b/c. Our results suggested that gestational inflammation accelerated age-related cognitive impairment and the decline of PSD-95, GluA1, and Homer-1b/c protein expression, and postpartum EE could alleviate these changes.